Edukasi Budaya Organisasi Kepada Anggota Fatayat Nu Desa Sambirejo Pare Kediri - Fadhil Akbar; Setyo Herlambang, Ganang; Jazuli, M.Nafi’udin (LP3M IAIFA Kediri, 2023)
The application of educational methods is effective in educating members of Islamic Organizations to better understand the Organizational Culture of the Organization itself. Because individual teaching and learning activities can increase the activeness of students in discussing problems and solving them, the application of this method will cause a diverse learning process. This diversity will be a wealth of knowledge to be studied more deeply. The research approach used in this study is the PAR method or Participatory Action Research. The general objective of this program is to provide Organizational Culture Education.